Dismantling Promoter-driven RNA Polymerase II Transcription Complexes in Vitro by the Termination Factor Rat1 - Pearson, Erika L. (American Society for Biochemistry and Molecular Biology, 2013)
Proper RNA polymerase II (Pol II) transcription termination is essential to generate stable transcripts, to prevent interference at downstream loci, and to recycle Pol II back to the promoter (1–3). As such, termination is an intricately controlled process that is tightly regulated by a variety of different cis- and trans-acting factors (4, 5). Although many eukaryotic termination factors have been identified to date, the details of the precise molecular mechanisms governing termination remain to be elucidated. We devised an in vitro transcription system to study specific Pol II termination. We show for the first time that the exonucleolytic Rat1·Rai1 complex can elicit the release of stalled Pol II in vitro and can do so in the absence of other factors. We also find that Rtt103, which interacts with the Pol II C-terminal domain (CTD) and with Rat1, can rescue termination activity of an exonucleolytically deficient Rat1 mutant. In light of our findings, we posit a model whereby functional nucleolytic activity is not the feature of Rat1 that ultimately promotes termination. Degradation of the nascent transcript allows Rat1 to pursue Pol II in a guided fashion and arrive at the site of RNA exit from Pol II. Upon this arrival, however, it is perhaps the specific and direct contact between Rat1 and Pol II that transmits the signal to terminate transcription.